Why are Filipinos killing fellow Filipinos? we as a people have divided into two nations and become a country at war with itself - Almonte, Jose T. (Foundation for Economic Freedom, 2008)
Publisher's note: "This pamphlet is our initial effort to bring to a wider-and younger-audience the book, 'To put our house in order we must level the playing field, by Jose T. Almonte', who was National Security Adviser to President Fidel V. Ramos in 1992-98. The book, when it appeared in June 2007, immediately evoked widespread attention and interest that continues until now, for its unflincing attempt to understand what we as a people are, and what we have become. In the original book, the main essays here appeared as the introduction; the others are the transcripts of speeches deliverd at the book launching, held at Club Filipino's Kalayaan Hall, on 16 August 2007. The introduction, in our view, fulfills adequately its function of summing up the book's central argument and inviting the reader to examine closely the thesis presented in the book proper. The speeches are commentaries on the writer, the country, and out times" -- p. [3].